DETEKSI VIRUS DEN3 PADA SEMUA STADIUM Aedes aegypti (TRANSOVARIAL) DENGAN TEKNIK IMUNOSITOKIMIA SECARA INVITRO - Kumoro Setya, Adhi; Dharmawan, Ruben (Jurnal Farmasi (Journal of Pharmacy), 2016)
Many dangerous parasites transmitted by the mosquito, one of which is dengue virus which causes dengue fever. The previous study said that in immunocytochemistry, dengue virus can be found in A. aegypti that does not suck blood. The basic principle of this examination was done by a technique of determining the existence (location) of antigen in cells in a tissue using antigen-antibody reaction. The purpose of this study was to determine the result of positive value of A. aegypti breeding stages in laboratory scale. DEN3 virus was mixed into the blood for trial then infected orally on the A. aegypti for breeding. All stages of breeding results was tested for DEN3 virus from the body tissue. DEN3 antigen in the body of the vector will bind with specific antibody from reagent and by the presence of the enzyme and chromogen substrate, it will give a brown color to the cells and granule surrounding the cells. Such color reaction was checked using a light microscope with 400x magnification with the positive control of DEN3 breed and the negative control of normal blood as a comparison. The findings showed that immunocytochemistry with SBPC method was capable of detecting DEN3 at all stages of metamorphosis of A. aegypti with the results of the stage respectively; egg: 82%, larva: 89%, pupa: 94% and adult: 100%. These results showed how immunocytochemistry technique as an alternative method which is relatively cheaper than molecular technique can be used for surveillance on dengue will appear.